Optimizing sustainable and multifunctional management of Alpine Forests under climate change - Leo Gallus Bont; Michael Hölscher; Simon Mutterer; Maria Beranek; Janine Schweier; Udo Buscher; Martin Scheffler; Kai Husmann; Leona Ottens; Clemens Blattert (Scientific Reports)
Abstract Climate change is challenging the sustainable provision of biodiversity and ecosystem services in mountain forests, including the important protection service against gravitational natural hazards. Forests offer a relatively cost-efficient measure to protect humans and infrastructure from natural hazards. Forest managers are faced with the question of how to adapt their forest to climate change and optimally manage their forests to guarantee future forest multifunctionality. Usually, alternative close-to-nature forest management strategies can be implemented, but individual management objectives and forest resilience affect the optimal portfolio of management strategies. To address this planning task, we used the climate-sensitive forest growth model ForClim and developed a tailored multi-objective optimization method, considering particularities of forests with a protection service. We applied the method in an Alpine forest enterprise in Switzerland. We combined three climate change scenarios with three optimization scenarios. Our results show that a diversified and optimized portfolio of management strategies can safeguard and improve the provision of multiple ecosystem services and biodiversity concurrently. However, given the increasing intensity of climate change, a greater share of climate-adapted close-to-nature forest management strategies is necessary, reaching 78% in forests without a protection service and 68% in forests with a protection service under severe climate change and optimized for multifunctionality. Adaptation also enabled further improvement of biodiversity and ecosystem service provision, particularly for carbon sequestration. The presented simulation and optimization framework, tailored for mountain forests with a protection service, shows flexibility in the integration of management objectives, making it useful for decision support. Forest management planning should rely more on and make use of such frameworks to help support forests under the uncertainties of climate change and to achieve the future political ambitions of multifunctionality and climate resilient forest ecosystems.